PENGARUH PENAMBAHAN BENTONIT PADA ABU VULKANIK SEBAGAI PASIR CETAK TERHADAP PERMEABILITAS DAN KEKUATAN TEKAN UNTUK SUPLEMEN MODUL PEMBELAJARAN MATA KULIAH TEKNIK PENGECORAN - Multahada, Adib (Jurnal Nosel, 2015)
The purpose of this study was to determine: (1) The effect of adding bentonite to the permeability of the vulcanic ash. (2) The effect of adding bentonite to the compressive strength of the vulcanic ash. The reseach was conducted at Manufactur Polyteknik, Ceper, Klaten. The reseach method is experimen method. The indipendent variable in this study is the variation of  bentonite with levels of 0%, 5%, 4%, 8%, and 12% and the dependent variable is the permeability and compressive strength. The results of this  study were: (1) The addition of bentonite in the molding sand decreased the permeability. (2) The addition of bentonite comes increased compressive strength. (3) Variations bentonite with levels of 0%, 4%, 8% and 12% for successive bentonite 14,07; 13,50; 13,37; dan 10,37 cm3/minute, while for compressive strength of successive contributed 51,33; 57,90; 64,27, and 72,73 KN/m2. The smallest permeability occurs at levels of 12% bentonite  is 10,37 cm3/menit  and compressive strength variation in the levels of 0% is 51,33 KN/m2, While most the permeability occurred at 0% bentonite are 14,07 cm3/menit and compressive strength in the bentonite levels 12% ie 72,73 KN/m2.